Amber on the Mountain - Johnston,Tony; Duncan, Robert (New York, 1994)
Isolated on her mountain, Amber meets and befriends a girl from the city who gives her the determination to learn to read and write.
richter Elem. Accel. Reader
4.3
Keywords: Literacy; Fiction; Friendship; Fiction; Mountain life; Fiction